Values of Progressive Islamic Education and Multicultural Education in Alaq: 1-5 - Salahudin; Syamsul Hidayat; Muthoifin; Ismail Abdul Ghani al-Jalal (Walidem Institute and Publishing (WIP), 2023)
This study aims to discuss the values of Islamic education progress and multicultural education in the Qur'an Surat al-Alaq verses 1-5. This research is motivated by three main points. First; weak literacy in the sense that Muslims are less able to apply knowledge, analyze, and solve problems in a variety of problems. Second; Lack of appreciation in actualizing transcendence. Third; The dichotomy between science and Islam. Fourth, a lack of fondness for writing to produce scientific work, fifth, a decline in moral values. So it is very necessary to review and live the values of advanced Islamic Education contained in Q.S Al-Alaq verses 1-5 by looking at the glasses of Tafsir Tarbawi. This type of research is library research. This research approach is to focus on historical, philosophical, and data analysis approaches using content analysis. The results of this study conclude that in improving the values of Islamic education progress and multicultural education there is a need for literacy, integration and transparency, habitualization, and read-write. These four components are central to application in the world of education, especially Islamic education.